(untitled) (Economics and region, 2025)
The article reveals the scientific and theoretical foundations of accounting and auditing of grant activities in higher education institutions through the lens of bibliometric analysis. It is noted that under conditions of limited budget financing and the intensification of international cooperation, grants play an important role in the strategic development of universities, providing not only financial support for research projects but also enhancing the competitiveness of national higher education in the global arena. At the same time, it is emphasized that the processes of accounting, control, and auditing of attracted grant resources remain fragmentarily studied in the academic environment, requiring a comprehensive rethinking and revision of methodological approaches. The purpose of the study is to conduct a bibliometric analysis of scientific publications in the Scopus database related to accounting and auditing of grant activities, with a focus on identifying key trends and dominant directions in this research field. The methodological basis of the study is the use of VOSviewer software to construct scientometric maps and analyze key concepts. The results of the research show that despite the growing interest in the topic, the scientific landscape remains fragmented and is characterized by a low level of interdisciplinary integration. Among the leaders in terms of the number of publications are research teams from the United States, the United Kingdom, China and countries of the European Union. Thematic clusters mainly cover accounting-financial, gender, health, and communication aspects of this issue. The scientific novelty lies in the application of bibliometric methods to identify scientific trends, shape an understanding of the development of the accounting-auditing paradigm in the field of grant financing, and outline research prospects in the context of the advancement of international project activities of educational institutions. The practical significance of the study is that its results can be used at both the theoretical and practical levels of accounting and analytical support for grants, the development of methodological provisions for transparency and accountability policies, as well as in the formation of financial strategies for universities in the context of sustainable development.